Road Safety for All Road Users – Current Situation and Perspectives for 2030 - Alina Burlacu F.; Adrian Burlacu; Pop Horațiu (Romanian Journal of Transport Infrastructure, 2023)
This article presents a brief overview of Romania’s road infrastructure and road safety situation in general, and outlines perspectives for reducing the number of lives lost in road crashes by 2030. Romania’s road fatality rate per 100,000 population has improved overall from a 2008 high of around 15 to the current 2020 value of 8,5. However, despite a 30,8% reduction in road deaths during the past decade, Romania’s total annual number of road deaths has remained at an average of around 1890 fatalities per annum over this period, and compared to the EU average of 36,7%, Romania is positioned among the worst performing countries in the European Union (EU) in recent years in terms of road safety. A World Bank road safety management capacity review performed in 2016 found a series of factors to be contributing to this high number of road deaths, such as inadequate political commitment to effective actions to reduce road fatalities, fragmented government road safety activities across a number of regulatory entities, speed limits set at levels that exceed internationally accepted survivable limits, weak traffic law enforcement including a lack of speed enforcement cameras resulting in a failure of drivers to comply with speed limits, and a lack of structured programs to implement human error tolerant road infrastructure constructed according to Safe System principles. A series of recommendations from the capacity review were adopted since 2016, although much remains to improve road safety in Romania, especially in light of the Second Decade of Action for Road Safety 2021-2030 and the United Nations Sustainable Goals.